2018
DOI: 10.4155/fsoa-2017-0098
|View full text |Cite
|
Sign up to set email alerts
|

Fascin is Secreted in Male’s Serum: Results of a Pilot Study

Abstract: Aim:Fascin is a 55 kDa globular protein with an important role in cell migration. Aim of study was to investigate serum fascin in healthy males.Materials & methods:From 1 July 2016 to 31 December 2016, we collected serum from 46 males. Serum fascin level was performed using ELISA kit from USBiological (Salem, MA, USA).Results:Median age was 64 years. Mean fascin serum level was 9.84 ng/ml, mean prostate-specific antigen (PSA) was 2.74 ng/ml and mean prostate volume was 37.64 cc. The 51–60 years group had a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Furthermore, we found a positive correlation between FSCN1 levels measured in serum and in the primary ACC mass. The levels found in non-tumoral patients in our studies are in agreement with those reported in similar studies performed in healthy subjects (13) and in other cancers (14) and lower than 10 ng/ml. Moreover, serum FSCN1 levels were significantly higher in ACC patients compared with obese/T2D patients, who have higher levels of FSCN1, probably due to kidney overload/damage associated to diabetes, as already demonstrated in renal injury associated with renal transplantation (15).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we found a positive correlation between FSCN1 levels measured in serum and in the primary ACC mass. The levels found in non-tumoral patients in our studies are in agreement with those reported in similar studies performed in healthy subjects (13) and in other cancers (14) and lower than 10 ng/ml. Moreover, serum FSCN1 levels were significantly higher in ACC patients compared with obese/T2D patients, who have higher levels of FSCN1, probably due to kidney overload/damage associated to diabetes, as already demonstrated in renal injury associated with renal transplantation (15).…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that serum levels of FSCN1 did not differ between PCa patients and controls, and these findings are in accordance with the results of data mining performed on TCGA-PRAD dataset. In contrast, similar serum FSCN1 determinations, performed in patients diagnosed with lung cancer, laryngeal carcinoma and hepatocellular carcinoma, were correlated to tumor aggressiveness [ 32 , 38 , 49 ]. Teng et al were the first to investigate serum FSCN1 in patients with cancer, utilizing an ELISA kit for human FSCN1 from USCN Life Science (TX, USA) and reporting higher values in patients with NSCLC compared with healthy controls (which reported a median value of 3 ng/ml) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As results, our mean FSCN1 serum level reported for healthy controls was 7.33 ng/ml. However, normal FSCN1 serum levels were shown to be 9.43 ng/ml, in a recently published article [ 49 ]. Similarly, FSCN1 serum levels identified by Elewa et al in healthy males was 9.9 ng/ml while patients with hepatocellular carcinoma showed a mean FSCN1 serum level of 14.8 ng/ml which was significantly higher compared with levels reported in controls and in cirrhotic participants [ 49 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations